The reality of using e-learning at the University of Hama from the students’ point of view (Journal of Hama University, 2025)
The following research aims to determine the current reality of the application of e-learning at Hama University in terms of technological infrastructure, curricula, and faculty members' competencies from the students' point of view, in addition to identifying the main challenges facing the application of e-learning at Hama University, and identifying the available opportunities to develop and improve the application of e-learning at Hama University.A questionnaire was designed by the researcher consisting of three main axes: the reality of e-learning in terms of technological infrastructure, the reality of e-learning in terms of curricula, and the reality of e-learning in terms of faculty members' competencies, distributed over 21 items.The research sample consisted of 1500 male and female students from Hama University who were selected using the random sampling method from various colleges. The study reached the following results:The axis of faculty members' competencies obtained a weighted average of (2.83) with an agreement score, followed by the axis of technological infrastructure with a weighted average of (2.51) and an agreement score, and finally the axis of curricula with a weighted average of (2.54) and an agreement score.At the end of the study, in light of the previous results, the overall challenges of implementing e-learning were identified in several basic points, and the opportunities available for developing and improving the implementation of e-learning at Hama University were summarized.
Keywords: : E-learning ,University of Hama,Syria.